Combined multi-omics approach to identify the key metabolites, key microorganisms and biomarkers correlated with the neutrophil extracellular traps-associated gene TIMP1 in osteoarthritis - Xiang, Yaoyu; Li, Jizheng; Hu, Xidan; Yang, Xianguang; Sun, Fei; Yang, Jing; Ge, Weiqing; Zhou, Tao; Song, En (Frontiers in Pharmacology, 2025)
BackgroundNeutrophil extracellular traps (NETs) contribute significantly to osteoarthritis (OA) pathogenesis; however, the precise molecular interactions remain unclear. This study aimed to identify key NET-associated genes and their correlated metabolites and microbiota in OA through an integrated multi-omics approach.MethodsInitially, transcriptomic datasets were screened to identify NET-related genes implicated in OA. A rat OA model was established, and the expression of key genes was validated using RT-qPCR, histological analysis, and immunohistochemistry. TIMP1 was selected for further exploration via in vivo gene silencing. Subsequently, transcriptomics, metabolomics, and 16S rRNA sequencing were performed on serum, cartilage, and fecal samples from experimental animals. Differentially expressed genes (DEGs), microbiota, and metabolites associated with TIMP1 were identified through integrated bioinformatics analyses. Correlation analyses across omics data layers were conducted to pinpoint biomarkers, key metabolites, and microbial taxa.ResultsITGB1, ITGB2, MMP9, and TIMP1 emerged as key NET-associated genes, with TIMP1 being selected as the primary target. TIMP1 silencing significantly alleviated inflammatory responses and cartilage degradation in OA rats. Multi-omics analyses identified 6 biomarkers, 9 key metabolites (e.g., FAHFAs, 12-HETE, MTA, xanthosine), and 1 key microbial genus (Muribaculaceae) strongly correlated with TIMP1 expression. These molecular entities were enriched in pathways related to lipid metabolism, nucleotide turnover, immune regulation, and gut-joint crosstalk.ConclusionTIMP1 acts as a pivotal regulator in OA, influencing inflammation, cartilage remodeling, metabolic pathways, and gut microbiota composition. This study provides novel mechanistic insights and potential therapeutic targets for OA.